(untitled) (Research, Society and Development, 2023)
Anxiety Disorder (AD) is very prevalent, according to the WHO (world health organization) it is present in 9.3% of the Brazilian population. With the pandemic caused by COVID-19, there was a lot of tension in society, due to the need to adapt to a new reality of health crisis. This scenario abruptly interfered with medical training, requiring students and educators to adapt. Among the various changes, the migration of face-to-face teaching to the remote environment and the suspension of practical classes were included. This caused many academics to feel fear and anxiety about a situation they had not yet experienced, leading to psychic changes. Thus, in this study, a quantitative research was carried out through the application of scholars to medical students from an institution in the West of Paraná, with the objective of understanding what were the losses caused in their lives because of COVID-19 in terms of with respect to Anxiety Disorder (AD).